Mutation and expression of the C-KIT gene on population of Kazakhstan (International Journal of Biology and Chemistry, 2020)
Lung cancer is still a leading cause of death from malignant tumors worldwide. Due to late diagnosis, results of treatment remain unsatisfactory. In Kazakhstan about 3,669 new cases of lung cancer are detected every year, with a 5-year survival rate for 2016 equal to 48.0%. The aim of the current workis to study the expression of C-KIT protein and identify mutations in patients with lung cancer living in Almaty region. Literature data showed that anomalous expression of the corresponding gene and presence of mutations lead to a number of malignant neoplasms. Creation of drugs targeting C-KIT protein, promotes the development of clinical diagnosis and treatment of cancer. Blood samples and biopsy material obtained from patients diagnosed with lung cancer, treated at the Almaty Oncology Center and residing in Almaty region served the objects of the study. Written informed consent was obtained from all patients. Analysis of restriction fragment length polymorphism and immunohistochemical analysis followed the polymerase chain reaction. For immunohistochemical analysis tissue fixed in formalin and embedded in paraffin blocks was used. The presence of mutations in codon 557 was revealed by the genetic analysis of 11 exon of C-KIT gene. RFLP analysis and sequencing showed mutations in the codon. Immunohistochemical analysis revealed overexpression of C-KIT gene in four (9.09%) patients, 14 (31.82%) patients had moderate expression, 24 (54.54%) patients had weak expression and two (4.55%) patients had no expression. In total, 18 (40.91%) patients had a positive response to immunohistochemical analysis. This suggests that thedisorders occur in the cells of tumor tissue and are not inherited. In fact, in most cases the occurrence of lung cancer can be associated with smoking.